Microstructural characterisation of the Ypresian clays (Kallo-1) at nanometre resolution, using broad-ion beam milling and scanning electron microscopy. Issue 3 (27th May 2016) - Hemes, S.; Desbois, G.; Klaver, J.; Urai, J.L.
Abstract: Besides the Oligocene Boom Clay, the Ypresian clays – part of the Eocene Ieper Group (Kortrijk Formation and Kortemark Member) – are currently being investigated as an alternative host rock for the deep geological disposal of radioactive waste in Belgium and the Netherlands. In this study, broad-ion-beam milling and high resolution scanning electron microscopy (BIB-SEM) analyses were carried out to analyse the mineral fabrics and microstructures of representative Ypresian clay samples from different depths of the ON-Kallo-1 borehole (Kallo, Belgium). Qualitative microstructural observations indicate that mineral fabrics and pore morphologies in fine-grained samples are comparable to those found for fine-grained Boom Clay, but most of the Ypresian clay samples analysed also contained a significant silt fraction, which is associated with larger inter-aggregate pores, coated by a thin, very low porous clay layer. Quantitative pore-shape analysis shows lower axial ratios and elongations, as well as higher roundness and circularities for pores in the clay matrix of the more coarse-grained samples, compared to the fine-grained samples. The contribution of large pores (>1 × 10 7 nm² pore area) to the total BIB-SEM observed porosity was found to correlate with the non-clay mineral (NCM) content of a sample. Frequencies of pore sizes within the clay matrix follow a power-law distribution, hinting towards the possibility of up-scaling of the nanometre-scale observations to larger scale (micro-) structural features of the material. Power-law exponents are comparable to values found for power-law pore-size distributions within the clay matrix of the Boom Clay, which indicates similarity of the pore-space morphologies within the clay matrix of the Boom Clay and the Ypresian clays. Wood's metal injection, followed by (cooled BIB)-SEM analysis shows that all visible pores are connected via pore throats of diameter down to 10 nm.